Molecular phylogenetics reveals the evolutionary history of marine fishes (Actinopterygii) endemic to the subtropical islands of the Southwest Pacific - Samayoa AP; Struthers CD; Trnski T; Roberts CD; Liggins L (Elsevier Inc, 2022)
Remote oceanic islands of the Pacific host elevated levels of actinopterygian (ray-finned fishes) endemism. Characterizing the evolutionary histories of these endemics has provided insight into the generation and maintenance of marine biodiversity in many regions. The subtropical islands of Lord Howe, Norfolk, and Rangitāhua (Kermadec) in the Southwest Pacific are yet to be comprehensively studied. Here, we characterize the spatio-temporal diversification of marine fishes endemic to these Southwest Pacific islands by combining molecular phylogenies and the geographic distribution of species. We built Bayesian ultrametric trees based on open-access and newly generated sequences for five mitochondrial and ten nuclear loci, and using fossil data for time calibration. We present the most comprehensive phylogenies to date for marine ray-finned fish genera, comprising 34 species endemic to the islands, including the first phylogenetic placements for 11 endemics. Overall, our topologies confirm the species status of all endemics, including three undescribed taxa. Our phylogenies highlight the predominant affinity of these endemics with the Australian fish fauna (53%), followed by the East Pacific (15%), and individual cases where the closest sister taxon of our endemic is found in the Northwest Pacific and wider Indo-Pacific. Nonetheless, for a quarter of our focal endemics, their geographic affinity remains unresolved due to sampling gaps within their genera. Our divergence time estimates reveal that the majority of endemic lineages (67.6%) diverged after the emergence of Lord Howe (6.92 Ma), the oldest subtropical island in the Southwest Pacific, suggesting that these islands have promoted diversification. However, divergence ages of some endemics pre-date the emergence of the islands, suggesting they may have originated outside of these islands, or, in some cases, ages may be overestimated due to unsampled taxa. To fully understand the role of the Southwest Pacific subtropical islands as a 'cradle' for diversification, our study advocates for further regional surveys focused on tissue collection for DNA analysis.
Keywords: Endemism; Multi-locus data; Oceanic islands; Ray-finned fishes; Southwest Pacific; Time-calibrated phylogeny; Animals; Australia; Bayes Theorem; Biodiversity; Fishes; Phylogeny